Anticyclone Eddies Favor the Genesis of Off‐Season Tropical Cyclone in the Western North Pacific. Issue 1 (30th December 2022) - Zhan, Weikang; He, Qingyou; Zhang, Ying; Zhan, Haigang
Abstract: Mesoscale ocean eddies, which typically exhibit different heat and atmospheric conditions to their surroundings, significantly affect the path and intensity of tropical cyclones (TCs). By analyzing 27 years (1993–2019) of eddy and TC data, here we show that mesoscale eddies also play non‐negligible roles in the genesis of TCs (TCG). During the TC off‐season months of December to May, TCs generating over anticyclone eddies (AEs) clearly outnumber those over cyclone eddies (CEs) (14 vs. 6) in the western North Pacific, and featuring a further north location. Composite analysis also exhibits a higher genesis potential index ( G P I o c e a n GPI_ocean ) in AEs than that in CEs, indicative of a higher TCG probability over AEs especially under a relatively cooler oceanic background, which is mainly attributed to the eddy‐associated warming in the upper ocean. These results motivate future studies on better forecasting regional TC activities by considering the impacts of ocean eddies in air‐sea models. Plain Language Summary: Tropical cyclone (TC) is one of the most seriously disastrous weather systems. Its genesis mechanism is important and yet not been fully understood. Previous studies have attributed TC genesis (TCG) mainly to large‐scale climate variations, while our results here show that oceanic mesoscale eddies, ubiquitous energetic vortices with radius ranging from tens to hundreds of kilometers, can also affect TCG. During the TC off‐season (December–May), there are markedly much more TCs that generate over anticyclone eddies (AEs) than cyclone eddies (CEs) in the western North Pacific. The eddy composite analysis further shows a higher genesis potential index in AEs than that in CEs, indicative of a higher probability of TCG over AEs. The TCG difference between AEs and CEs exists mostly under a relatively cooler oceanic condition, and is mainly caused by eddy‐associated upper‐ocean temperature anomalies. These findings invite us to rethink the effects of local oceanic perturbations on TCG, and help to better forecast regional TC activities in eddy‐resolving models. Key Points: Tropical cyclones are more frequently generated over anticyclone eddies (AEs) than cyclone eddies in winter and spring The genesis potential index of the tropical cyclone in AEs is significantly higher than that in cyclone eddies Eddy‐associated upper‐ocean warming in AEs is the dominant process on the more frequent tropical cyclone genesis